KEJADIAN ANALISA KEMATIAN BAYI DENGAN ASFIKSIA DI RSUD dr. FAUZIAH DI KABUPATEN BIREUEN TAHUN 2015 - Warzukni, Seri; Djafri, Defriman; Sanusi, Sri Rahayu (JURNAL KESEHATAN ALMUSLIM, 2017)
Asphyxia of Neonatorum is failure of breath spontaneously and regular at the time of newborn baby or a few moments after baby born marked with situation of Pao2 in low blood (hypoxemia), hypercarbia ( Paco2 mount) and acidosis. Based on secondary data obtained from medical records researcher dr. Fauziah Bireuen district on infant mortality in 2015 was as much as 481 babies. Data analysis using logistic regression using Stata 12. The results showed bivariate variables significantly associated with infant mortality asphyxia, there are three variables significantly related ie parity (OR = 4.11 95% CI = 2.17 to 7.79, p = 0.000), Preeclampsia (OR = 7.57 95% CI = 3.79 to 15.1, p = 0.000), referring Lama (OR = 2.273 95% CI = 1.22 to 4.21 p = 0.009). Results of multivariate analysis obtained the most related variable is preeclampsia (OR = 6.41 95% CI = 2.95 to 13.90, p = 0.000).